The effect of cash conversion cycle, leverage, sales growth, and firm size on profitability in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX): Pengaruh siklus konversi kas, leverage, pertumbuhan penjualan, dan ukuran perusahaan terhadap profitabilitas pada perusahaan manufaktur sektor industri barang konsumsi yang terdaftar di bursa efek indonesia (BEI) - Zhafira Haura Putri Tomewi; Yolandafitri Zulvia (Universitas Negeri Padang, 2023)
This study aims to analyze the effect of (1) cash conversion cycle on company profitability, (2) leverage on company profitability, (3) sales growth on profitability, (4) firm size on profitability of manufacturing companies in the consumer goods industry sector listed on the Stock Exchange Indonesia in 2018-2021. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange. Meanwhile, the sample in this study was determined using the purposive sampling method, namely manufacturing companies in the consumer goods industry sector for four consecutive years from 2018-2021 so that a total sample of 52 companies was obtained with 186 observation data. The analytical method used is multiple linear regression method using the IBM SPSS Statistics 22 program. The results of this study conclude that (1) the cash conversion cycle has a negative and not significant effect on company profitability, (2) leverage has a negative and significant effect on company profitability, (3) sales growth has a positive and significant effect on company profitability, (4) firm size has a positive and significant effect on company profitability.